Vortex‐assisted dispersive liquid–liquid microextraction‐gas chromatography (VADLLME‐GC) determination of residual ketamine, nimetazepam, and xylazine from drug‐spiked beverages appearing in liquid, droplet, and dry forms. Issue 5 (26th May 2022) - Teoh, Way Koon; Mohamed Sadiq, Nabeesathul Sumayya; Saisahas, Kasrin; Phoncai, Apichai; Kunalan, Vanitha; Md Muslim, Noor Zuhartini; Limbut, Warakorn; Chang, Kah Haw; Abdullah, Ahmad Fahmi Lim
Abstract: Presently, investigations of drug‐facilitated crimes (DFCs) rely on the detection of substances extracted from biological samples following intake by the victim. However, such detection requires rapid sampling and analysis prior to metabolism and elimination of the drugs from the body. In cases of suspected DFCs, drug‐spiked beverage samples, whether in liquid, droplet, or even dried form, can be tested for the presence of spike drugs and used as evidence for the occurrence of DFCs. This study aimed to quantitatively determine three sedative‐hypnotics (ketamine, nimetazepam, and xylazine) from drug‐spiked beverages using a vortex‐assisted dispersive liquid–liquid microextraction‐gas chromatography (VADLLME‐GC) approach. In this study, a GC method was first developed and validated, followed by the optimization of the VADLLME protocol, which was then applied to quantify the target substances in simulated forensic case scenarios. The developed GC method was selective, sensitive (limit of detection: 0.08 μg/ml [ketamine]; 0.16 μg/ml [nimetazepam]; 0.08 μg/ml [xylazine]), linear ( R 2 > 0.99), precise (%RSD <7.2%), and accurate (% recovery: 92.8%–103.5%). Higher recoveries were achieved for the three drugs from beverage samples in liquid form (51%–97%) as compared to droplet (48%–96%) and dried (44%–93%) residues. The recovery was not hindered by very low volumes of spiked beverage and dried residues. In conclusion, the developed VADLLME‐GC method successfully recovered ketamine, nimetazepam, and xylazine from spiked beverages that are likely to be encountered during forensic investigation of DFCs.